2011
DOI: 10.1148/rg.315105081
|View full text |Cite
|
Sign up to set email alerts
|

Informatics in Radiology: Evaluation of an e-Learning Platform for Teaching Medical Students Competency in Ordering Radiologic Examinations

Abstract: A preliminary audit of orders for computed tomography was performed to evaluate the typical performance of interns ordering radiologic examinations. According to the audit, the interns showed only minimal improvement after 8 months of work experience. The online radiology ordering module (ROM) program included baseline assessment of student performance (part I), online learning with the ROM (part II), and follow-up assessment of performance with simulated ordering with the ROM (part III). A curriculum blueprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Howlett [13] decided to integrate the imaging into clinical cases to meet the requirements of the actual clinical cases and be able to create an essence of real clinical practice for students. Marshall [17] addressed radiological ordering practical matters with the ROM program to compensate conventional radiology curriculum at undergraduate level. Silveira [20] uses CEPH-learning software that addresses learning situations through complex and variety of real world case studies to be able to put knowledge into practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Howlett [13] decided to integrate the imaging into clinical cases to meet the requirements of the actual clinical cases and be able to create an essence of real clinical practice for students. Marshall [17] addressed radiological ordering practical matters with the ROM program to compensate conventional radiology curriculum at undergraduate level. Silveira [20] uses CEPH-learning software that addresses learning situations through complex and variety of real world case studies to be able to put knowledge into practice.…”
Section: Discussionmentioning
confidence: 99%
“…Among the customized tools and applications (n = 9) Radiation Protection (RP) module improved radiation protection knowledge [16], Radiological Ordering Module (ROM) improved quality of radiologic examination orders [17], I2Vote improved knowledge retention [18], and Online Electronic Information Skills OEIS developed skills in accessing the right radiology information [19]. The Learning Virtual Object LVO is seen to be of no importance in changing student performance but it did give significant results if used for longer duration [20].…”
Section: E-learning Initiativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a variety of breast receiver coils are available that yield differences in SNR, uniformity, comfort, subject orientation, unilateral imaging options, and biopsy devices . In 2010, Marshall et al studied three multicoil breast arrays for conventional and parallel imaging. They found that placing additional small, adjustable coil elements adjacent to the breast tissue led to a larger SNR.…”
Section: Mrs Acquisitionmentioning
confidence: 99%
“…Online independent learning modules are certainly considered more innovative [12,21,22] than printed textbooks. These resources allow more opportunity for active learning by providing an interactive experience with a case-based or problem-based format [3].…”
Section: Computer-based Simulations and E-learningmentioning
confidence: 99%